The small RNA mascRNA differentially regulates TLR-induced proinflammatory and antiviral responses - Tao Sun; Chunxue Wei; Daoyong Wang; Xuxu Wang; Jiao Wang; Yuqing Hu; Xiaohua Mao (JCI Insight, 2021)
MALAT1-associated small cytoplasmic RNA (mascRNA) is a highly conserved transfer RNA–like (tRNA-like) noncoding RNA whose function remains largely unknown. We show here that this small RNA molecule played a role in the stringent control of TLR-mediated innate immune responses. mascRNA inhibited activation of NF-κB and mitogen-activated protein kinase (MAPK) signaling and the production of inflammatory cytokines in macrophages stimulated with LPS, a TLR4 ligand. Furthermore, exogenous mascRNA alleviated LPS-induced lung inflammation. However, mascRNA potentiated the phosphorylation of IRF3 and STAT1 and the transcription of IFN-related genes in response to the TLR3 ligand poly(I:C) both in vitro and in vivo. Mechanistically, mascRNA was found to enhance K48-linked ubiquitination and proteasomal degradation of TRAF6, thereby negatively regulating TLR-mediated MyD88-dependent proinflammatory signaling while positively regulating TRIF-dependent IFN signaling. Additionally, heterogeneous nuclear ribonucleoprotein H (hnRNP H) and hnRNP F were found to interact with mascRNA, promote its degradation, and contribute to the fine-tuning of TLR-triggered immune responses. Taken together, our data identify a dual role of mascRNA in both negative and positive regulation of innate immune responses.